Impact of Islamic Authentication towards Traditional Ornaments in Great Mosques in West Java, Indonesia - Destiarmand, Achmad Haldani; Santosa, Imam (TAWARIKH, 2013)
ABSTRACT: Authenticity nowadays becomes a central issue concerning on identity and transformation. In the Islamic world and particularly in Indonesia, the phase of authenticity has become synonymous to the phase of revival, fanatism, and fundamentalism, following the previous phase of syncretism, secularism, and developmentalism. Within the context of Indonesian art and culture, authenticiy may cause interference in the spirit of preserving traditional values, including the roles, functions, and meanings traditional ornaments in contemporary mosques in West Java. To comprehend such interference, a synchronic historical analysis is conducted, supported by direct visual analysis towards physical evidence (artifacts) based on typology and aesthetic morphology approachs. This study aims at analyzing and finding the manifestation and impact of Islamic authentication towards the roles and functions of traditional ornaments in mosque architecture. Field analysis shows that the trends of forms, styles, roles, and functions of mosque ornaments have experienced a shift. The heterogenous traditional ornaments are getting ousted in favor of homogenous Arabesque ornaments. Mosque ornaments in West Java tend to adopt, copy, or imitate authentic Islamic identities oriented towards retrospective and enculturing images, in line with the spirit of Islamic revival whose foundation is a retrospective movement towards the Al-Qurâan, Al-Hadith, and the past glory of the classical Islam eras. KEY WORDS: Islamic authentication, ornaments, revivalism, typology and aesthetic approachs, city and regency, and great mosques in West Java.Â Â Â About the Authors: Achmad Haldani Destiarmand, M.Sn. is a Doctoral Candidate and Lecturer at the Faculty of Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10, Tamansari, Bandung, West Java, Indonesia; and Dr. Imam Santosa is a Senior Lecturer at the Faculty of Art and Design ITB. Corresponding author is: achmadhaldani@yahoo.comHow to cite this article? Destiarmand, Achmad Haldani & Imam Santosa. (2013). âImpact of Islamic Authentication towards Traditional Ornaments in Great Mosques in West Java, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.103-116. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 14, 2013); Revised (September 19, 2013); and Published (October 28, 2013).